Pollicipes caboverdensis sp. nov. (Crustacea: Cirripedia: Scalpelliformes), an intertidal barnacle from the Cape Verde Islands - Fernandes, Joana N. (2012)
Recently, genetic evidence supported the existence of a new species of the genus Pollicipes from the Cape Verde Islands, previously considered a population of P. pollicipes. However, P. pollicipes was not sampled at its southern limit of distribution (Dakar, Senegal), which is geographically separated from the Cape Verde Islands by about 500 km. Herein we describe Pollicipes caboverdensis sp. nov. from the Cape Verde Islands and compare its morphology with the other three species of Pollicipes: P. pollicipes, P. elegans and P. polymerus. Pollicipes pollicipes was sampled at both the middle (Portugal) and southern limit (Dakar, Senegal) of its geographical distribution. The genetic divergence among and within these two regions and Cape Verde was calculated through the analysis of partial mtDNA CO1 gene sequences. Pollicipes caboverdensis sp. nov. has a single whorl of capitular plates below the subrostrum, peduncular scales pointing up toward the capitulum and multi-articulate caudal appendages (all characters shared with P. pollicipes and P. elegans), reddish-orange capitular plates (large specimens), a single rostral median latus between the median latus and the rostrolatus (both characters shared with P. elegans), and uniquely possesses peduncular scales that are approximately the same width as height. The genetic distance between the Cape Verde population and the Senegal and Portugal populations is 13–14%, whilst between Senegal and Portugal it is < 1%.